Audit E-SPPD Diskominfo Kabupaten Mojokerto Menggunakan Framework COBIT 2019 - Aulia, Luluk Latifa; Satyareni, Diema Hernyka; Anugrah, Chandra Sukma (Ma'soem University, 2025)
The Mojokerto Regency Communication and Information Agency (Diskominfo) uses the E-SPPD application to automate the process of submitting, approving, and reporting civil servant (PNS) business trips. Since its implementation, this application has experienced several problems, including slow performance or inaccessibility at certain times, failed access, incompatibility with some devices, and incomplete system documentation. This study aims to measure the capability level of the E-SPPD application of the Communication and Information Agency of Mojokerto Regency using the COBIT 2019 framework, which focuses on the DSS01 (Manage Operations), DSS02 (Manage Service Requests and Incidents), and DSS03 (Manage Problems) domains. The methods used include structured interviews with several stakeholders determined through a RACI Chart. The results of data processing show that the average capability of the DSS01 domain is 4.2, which is at level 4 (Quantitative process), the DSS02 domain is 3.54, which is at level 4 (Quantitative process), and the DSS03 domain is 3.84, which is at level 4 (Quantitative process). The results of the study show that some processes have achieved the expected capabilities, while some processes, such as problem resolution documentation, are still below the expected level.